Impact of a Blended Periconception Lifestyle Care Approach on Lifestyle Behaviors: Before-and-After Study - van der Windt, Melissa; van der Kleij, Rianne Maria; Snoek, Katinka Marianne; Willemsen, Sten Paul; Dykgraaf, Ramon Henny Maria; Laven, Joop Stephanus Elisabeth; Schoenmakers, Sam; Steegers-Theunissen, Régine Patricia Maria (JMIR Publications, 2020)
BackgroundPericonception lifestyle behaviors affect maternal, paternal, offspring, and transgenerational health outcomes. Previous research in other target populations has shown that personalized lifestyle interventions, in which face-to-face counseling and eHealth ("blended care") are combined, may effectively target these lifestyle behaviors. ObjectiveWe aimed to assess the effectiveness of a periconceptional lifestyle intervention on the improvement of specific lifestyle components. MethodsA blended periconception lifestyle care approach was developed, combining the outpatient lifestyle counseling service "Healthy Pregnancy" with the eHealth platform "Smarter Pregnancy" (www.smarterpregnancy.co.uk) in which lifestyle was coached for 24 weeks. All couples contemplating pregnancy or already pregnant (≤12 weeks of gestation) who visited the outpatient clinics of the Department of Obstetrics and Gynecology at the Erasmus University Medical Center (Erasmus MC), Rotterdam, the Netherlands, between June and December 2018, were invited to participate. We measured changes in lifestyle behaviors at weeks 12 and 24 compared with baseline. Generalized estimating equations were used to analyze the changes in lifestyle behaviors over time. Subgroup analyses were performed for women with obesity (BMI ≥30 kg/m2), women pregnant at the start of the intervention, and those participating as a couple. ResultsA total of 539 women were screened for eligibility, and 450 women and 61 men received the blended periconception intervention. Among the participating women, 58.4% (263/450) were included in the preconception period. Moreover, 78.9% (403/511) of the included participants completed the online lifestyle coaching. At baseline, at least one poor lifestyle behavior was present in most women (379/450, 84.2%) and men (58/61, 95.1%). In the total group, median fruit intake increased from 1.8 to 2.2 pieces/day (P<.001) and median vegetable intake increased from 151 to 165 grams/day (P<.001) after 24 weeks of online coaching. The probability of taking folic acid supplementation among women increased from 0.97 to 1 (P<.001), and the probability of consuming alcohol and using tobacco in the total group decreased from 0.25 to 0.19 (P=.002) and from 0.20 to 0.15 (P=.63), respectively. Overall, the program showed the strongest effectiveness for participating couples. Particularly for vegetable and fruit intake, their consumption increased from 158 grams/day and 1.8 pieces/day at baseline to 190 grams/day and 2.7 pieces/day at the end of the intervention, respectively. ConclusionsWe succeeded in including most participating women in the preconception period. A high compliance rate was achieved and users demonstrated improvements in several lifestyle components. The blended periconception lifestyle care approach seems to be an effective method to improve lifestyle behaviors. The next step is to further disseminate this approach and to perform a randomized trial to compare the use of blended care with the provision of only eHealth. Additionally, the clinical relevance of these results will need to be substantiated further.